In vitro synergism of β-lactams with ciprofloxacin and moxifloxacin against genetically distinct multidrug-resistant isolates of Pseudomonas aeruginosa - Kanellakopoulou, Kyriaki; Galani, Irene; Giamarellou, Helen J.; Giamarellos-Bourboulis, Evangelos J.; Sarafis, Pavlos (My University, 2008)
In vitro combinations of β-lactams with fluoroquinolones against multidrug-resistant (MDR) Pseudomonas aeruginosa were tested. From a total of 200 isolates, 24 genetically distinct isolates defined by pulsed-field gel electrophoresis (PFGE) were selected. The isolates were exposed over time to imipenem, meropenem and ceftazidime as well as to their combinations with ciprofloxacin and moxifloxacin. All isolates were resistant to all agents tested at concentrations equal to their average serum level. Synergy of any of the tested combinations was found in 10 isolates (41.7%). This was shown after 4 h and 6 h of exposure accompanied by re-growth after 24 h. Not all the tested combinations were active against the same isolates. The combinations of imipenem + ciprofloxacin, ceftazidime + ciprofloxacin and imipenem + moxifloxacin were the most active. When time–kill assays were repeated for the latter isolates at antimicrobial concentrations equal to their maximum serum levels, synergy was prolonged to 24 h. The present findings should be interpreted with caution for the management of infections by MDR P. aeruginosa. They underscore the potential interest of reporting synergism between β-lactams and fluoroquinolones in the nosocomial setting when a MDR isolate emerges.
Keywords: Ceftazidime; Carbapenems; Ciprofloxacin; Moxifloxacin; Pseudomonas aeruginosa; Resistance